Therapy and Rehabilitation of Patients with Pulmonary Tuberculosis and Different Treatment Adherence - N. V. Rubleva; V. M. Kolomiets; E. Ya. Kochetkova (Антибиотики и Химиотерапия, 2020)
The pulmonary tuberculosis process as dependent on the disease form and the therapy efficacy with the use of Cycloferon in the treatment scheme were investigated. The study had two stages. At the first stage the data concerning 358 patients with primary pulmonary tuberculosis and infiltration (93 patients) or degradation (89 patients) and 176 patients with pulmonary fibrocavernous tuberculosis were analysed. At the second stage the efficacy of the treatment schemes applied to the patients with pulmonary fibrocavernous tuberculosis was compared. The etiotropic therapy intensive phase was applied to all the patients. Moreover, 56 patients (group 1) under the therapy and rehabilitation were treated with Cycloferon in a dose of 0.25 administered intramuscularly twice a week (not less than 16 injections for the course), 60 patients (group 2) were treated with Omega 3, 30 patients (group 3) were given the standard complex (vitamins and tonics), 30 patients (group 4) were under the etiotropic therapy alone. The following additional factors promoting progression and aggravation of the tuberculosis process were confirmed: degradation at the time of the disease diagnosis, high resistance of the pathogen to antituberculosis drugs, low adherence to the treatment, social desadaptation and especially psychofunctional state of the patients. The use of Cycloferon in the schemes of the intensive phase treatment of the primary fibrocavernous tuberculosis resulted in reduction of the intoxication signs, bacteria isolation, positive dynamics of the cavity healing, lower lung infiltration and consequently high frequency of the treatment positive outcomes (94.1+3.33%).